Obstructive sleep apnea combined dyslipidemia render additive effect on increasing atherosclerotic cardiovascular diseases prevalence. Issue 1 (December 2016) - Cao, Zhiyong; Zhang, Ping; He, Zhiqing; Yang, Jing; Liang, Chun; Ren, Yusheng; Wu, Zonggui
Abstract Background Current study was designed to investigate the effects of obstructive sleep apnea (OSA) combined dyslipidemia on the prevalence of atherosclerotic cardiovascular diseases (ASCVD). Methods This was a cross-sectional study and subjects with documented dyslipidemia and without previous diagnosis of OSA were enrolled. Polysomnography was applied to evaluate apnea-hypopnea index (AHI). Based on AHI value, subjects were classified into four groups: without OSA, mild, moderate and severe OSA groups. Clinical characteristics and laboratory examination data were recorded. Relationship between AHI event and lipid profiles was analyzed, and logistic regression analysis was used to evaluate the effects of OSA combined dyslipidemia on ASCVD prevalence. Results Totally 248 subjects with dyslipidemia were enrolled. Compared to the other 3 groups, subjects with severe OSA were older, male predominant and had higher smoking rate. In addition, subjects with severe OSA had higher body mass index, waist-hip ratio, blood pressure, and higher rates of overweight and obesity. Serum levels of fasting plasma glucose, glycated hemoglobin, LDL-C and CRP were all significantly higher. ASCVD prevalence was considerably higher in subjects with severe OSA. AHI event in the severe OSA group was up to 35.4 ± 5.1 events per hour which was significantly higher than the other groups (P  < 0.05 for trend). Pearson correlation analysis showed that only LDL-C was positively correlated with AHI events (r  = 0.685, P  < 0.05). Logistic regression analysis revealed that in unadjusted model, compared to dyslipidemia plus no-OSA group (reference group), OSA enhanced ASCVD risk in subjects with dyslipidemia, regardless of OSA severity. After extensively adjusted for confounding variables, the odds of dyslipidemia plus mild-OSA was reduced to insignificance. While the effects of moderate- and severe-OSA on promoting ASCVD risk in subjects with dyslipidemia remained significant, with severe-OSA most prominent (odds ratio: 1.52, 95 % confidence interval: 1.13–2.02). Conclusion OSA combined dyslipidemia conferred additive adverse effects on cardiovascular system, with severe-OSA most prominent.